Two‐Color Valence‐to‐Core X‐ray Emission Spectroscopy Tracks Cofactor Protonation State in a Class I Ribonucleotide Reductase. (4th September 2018) - Martinie, Ryan J.; Blaesi, Elizabeth J.; Bollinger, J. Martin; Krebs, Carsten; Finkelstein, Kenneth D.; Pollock, Christopher J.
Abstract: Proton transfer reactions are of central importance to a wide variety of biochemical processes, though determining proton location and monitoring proton transfers in biological systems is often extremely challenging. Herein, we use two‐color valence‐to‐core X‐ray emission spectroscopy (VtC XES) to identify protonation events across three oxidation states of the O2 ‐activating, radical‐initiating manganese–iron heterodinuclear cofactor in a class I‐c ribonucleotide reductase. This is the first application of VtC XES to an enzyme intermediate and the first simultaneous measurement of two‐color VtC spectra. In contrast to more conventional methods of assessing protonation state, VtC XES is a more direct probe applicable to a wide range of metalloenzyme systems. These data, coupled to insight provided by DFT calculations, allow the inorganic cores of the Mn IV Fe IV and Mn IV Fe III states of the enzyme to be assigned as Mn IV (μ‐O)2 Fe IV and Mn IV (μ‐O)(μ‐OH)Fe III, respectively.